Optimism and Self-Control : Complementary Predictors of Financial Risk-Taking Propensity Among Working Adults - Glenda Rodrigues, Crystal; B. V., Gopalakrishna (Indian Journal of Finance, 2023)
Purpose : The article aimed to investigate the complementary strength of two behavioral traits, namely, optimism and self-control, on the financial risk-taking propensity of working adults in India. In addition, the moderating effect of gender on the relationship of optimism and self-control with financial risk-taking propensity was examined. Methodology : The study adopted a cross-sectional-based survey approach with a sample consisting of 522 individuals of age 18 and above with diverse demographic characteristics. Purposive and convenience sampling techniques were employed for collecting data through a self-administered questionnaire. Structural equation modeling (SEM) was used to test the study’s hypotheses using the IBM AMOS software. Findings : The results revealed a positive association between optimism and financial risk-taking, while self-control showed a negative association. Further, the relationship between optimism and risk-taking propensity was moderated by gender, and this relationship was more pronounced among females. The study also revealed a contradictory finding which showed greater levels of optimism among females compared to males as opposed to prior research findings. Practical Implications : The study finds its importance among academicians who want to explore the complementary strengths of optimism and self-control in various other decision-making contexts. Financial service providers can look into the behavioral traits of optimism and self-control of their clients while assisting them in making financial decisions. Originality : The present study is unique as optimism and self-control as complementary predictors of the financial risk-taking propensity of working individuals have not been explored in the Indian context.